Nurse’s self-efficacy in patient engagement during the covid-19 pandemic - Fauziyah, Nuridha; Sri Hariyati, RR Tutik; Farida Rachmi, Shanti; Nopiana, Inna (Jurnal Keperawatan, 2023)
Introduction:  Active patient involvement is part of a patient centered care approach that must be facilitated by all health care providers, including in the hospitals. The concern of nurses being exposed by the Covid-19 virus during this pandemic is one of obstacle and challenging during providing patient engagement in nursing care.  Patient engagement is a methode to facilitate and support patient involvement in the care process by making patients as an active partner in improving their quality of care. Objectives: This study aims to determine the relationship between nurse self-efficacy and patient engagement in nursing care during the Covid-19 pandemic. Methods: This study used a cross sectional research design.  The respondents in this study were all nurses in the inpatient room, whether it was a Covid or non-Covid inpatient room, totaling 238 nurses.  Data collection in this study was carried out using an online questionnaire: the Self-Efficacy in Patient Centeredness Questionnaire (SEPCQ-27) and the Patient Engagement Index (PEI) questionnaire which had been modified by the researcher. Results: The results of bivariate analysis using Pearson correlation showed that there was a significant relationship between nurse self-efficacy and patient engagement (p < 0.001). Conclusions: Nurses' self efficacy in engaging patients is an important internal factor for nurses to support optimal patient participation and active involvement in the nursing care process.